Pelatihan Teknologi Budidaya dan Pengelolaan Penyakit Ramah Lingkungan Pada Tanaman Lada - Endang Mugiastuti; Loekas Soesanto; Abdul Manan (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2018)
Pepper is an important commodity and has high economic value. This commodity has begun to be cultivated by members of the PKK RT 07 and PKK RT 09, Tambak Sogra Village, Sumbang District, Banyumas Regency, in an effort to increase the use of the yard and increase family income. However, the knowledge and skills of PKK members regarding cultivation and diseases of pepper plants as well as effective and environmentally friendly management efforts are very low. The activity aimed was to improve knowledge and skills of members of the PKK group in the cultivation and management of pepper disease that are effective and environmentally friendly. Activities carried out with dissemination, training, and technology demonstration plots. The activities were able to increase the knowledge and skills of members of the PKK group in pepper cultivation and the management of the disease which is environmentally friendly. In addition, the application of Trichoderma sp. and Pseudomonas fluorescens in the demonstration plot can increase the growth of pepper.